2009
DOI: 10.1007/s00431-009-0995-z
|View full text |Cite
|
Sign up to set email alerts
|

Caloric intake and weight gain in a neonatal intensive care unit

Abstract: The aim of this paper was to study the weight gain in very-low-birthweight (VLBW) infants by adopting earlier and higher intake of proteins and earlier intake of lipids. We studied 28 VLBW infants admitted to Neonatal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In addition, Jadhav et al [14] demonstrated that any acidosis during early postnatal life occurs irrespective of dose and duration of parenteral amino acid administration. Multiple retrospective analyses [15][16][17][18][19][20][21][22][23][24] also have confirmed the beneficial effects described in the previous prospective studies. Most analyses were comparisons of epochs after nutritional policy had been changed.…”
Section: Parenteral Amino Acid Administration In Early Postnatal Phasesupporting
confidence: 83%
“…In addition, Jadhav et al [14] demonstrated that any acidosis during early postnatal life occurs irrespective of dose and duration of parenteral amino acid administration. Multiple retrospective analyses [15][16][17][18][19][20][21][22][23][24] also have confirmed the beneficial effects described in the previous prospective studies. Most analyses were comparisons of epochs after nutritional policy had been changed.…”
Section: Parenteral Amino Acid Administration In Early Postnatal Phasesupporting
confidence: 83%
“…However, smaller sample sizes can be preferable if it means that more attention is given to characterizing confounding factors (40). The observational studies included some with a before-and-after study design (24,26,29). With these studies, it was not possible to exclude the possibility that any changes in outcome may have occurred as a result of other factors that changed over time rather than the intervention.…”
Section: Early Parenteral Nutrition In Preterm Infantsmentioning
confidence: 99%
“…During introduction and advancement of enteral feeds to full feedings, withholding of enteral feedings results in delays in achieving full enteral feedings. 38 -40 Dinerstein et al 39 reported that 25% of preterm infants in their study experienced interruptions in their enteral feedings on an average of 3 to 4 days during feeding advancement. Extremely preterm infants are at higher risk for the withholding of feedings.…”
Section: Consequences Of Gastric Residualsmentioning
confidence: 96%
“…Collins et al 38 reported the median number of days feedings were withheld in these specific infants was 8. Interruptions in enteral feedings are associated with decreased caloric intake 40 and a decreased rate of growth 38 because adjustments to nutritional intake often do not occur in response to these interruptions. For example, a concomitant increase in the TPN rate may not occur.…”
Section: Consequences Of Gastric Residualsmentioning
confidence: 99%